The Effectiveness of Mindfulness- Based Metaphors in Molavi's Masnavi on Components of Psychological Capital among Depressed Female Students - Fatemeh Eslahi farshami; Ali Asghar Asgharnejad Farid; Khadijeh Abolmoali Alhosseini; javad khalatbari (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2021)
The present study was conducted to determine the effectiveness of mindfulness training based metaphors of Molavi's Masnavi on components of psychological capital among depressed female students. In this study, to extract the metaphors of Molavi's Masnavi, directional qualitative content analysis and quantitative content analysis were used with MAXQDA software. The identified codes were validated by coders' reliability method by 5 psychologists who were approved with a degree of agreement of 0.85% and were replaced in the mindfulness protocol. In terms of data collection techniques, the research method was quasi-experimental with pre-test-post-test with a control group and one-month follow-up. The statistical population included 195 female students who were psychology students of Chalous branch in 2019-2020 academic year. Forty students were selected through purposive sampling method that achieved high scores in Beck Anxiety Inventory (BAI) and were randomly assigned to experimental and control groups (20 people in each group). The content of mindfulness therapy sessions based on metaphors of Molavi's Masnavi was performed in 8 sessions of 90 minutes for the experimental group. Data analysis was performed using SPSS-22 software and mixed analysis of variance method. The results of statistical analysis showed that there was a significant difference (p <0.05) between the mean components of psychological capital (self-efficacy, resiliency, hope and optimism) in the experimental and control groups and also maintained its status in a one-month follow-up. Thus, it can be concluded that mindfulness therapy- based metaphors of Molavi's Masnavi improves the psychological capital of depressed female students.